DIABETES MELITUS DENGAN INSOMNIA DITINJAU DARI KARAKTERISTIK PASIEN DI PUSKESMAS BALOWERTI KEDIRI - Setiawan Wahyuningsih, Atik; Fitria Nusantara, Ana (JURNAL KEPERAWATAN BINA SEHAT, 2017)
ABSTRACTBackground: Diabetes mellitus is one of the co-morbidities of insomnia. Age and gender affect the setting of alpha waves during the sleep period, although the psychological factor is also a role that can’t be overridden by the occurrence of insomnia. This study aimed to identify the characteristics of patients with diabetes mellitus with insomnia in PHC Balowerti Kediri.Methods: The study design was observational. Samples were taken using total sampling technique. Measuring instrument used was questionnaires filled in accordance with the real conditions of the respondents. The data obtained were analyzed with frequency distribution and average.RESULTS: Of the 65 patients with diabetes suffer from insomnia, the data found that on average respondents aged 56.9 years, on average, suffered from diabetes mellitus for 6 years and 68.7% were female.Conclusion: The average age of 56.9 years, the average had diabetes mellitus for 6 years and more than most women.Suggestion: It is expected provide additional education about the frequency and characteristics of the incidence of diabetes with insomnia in patients with diabetes mellitus and its treatment without compromising the four pillars of the treatment of diabetes mellitusKeywords: Insomnia, Diabetes Mellitus, Characteristics